(untitled) (Repertorio Científico, 2024)
The teaching of mathematics in Costa Rica considers the demonstration in the school curriculum, from secondary to university education, in accordance with international standards embodied in the curricula of secondary education and the models of each university, but the practices associated with argumentation based on logic and deduction represent a challenge for students and teachers at all levels. It is intended in this reflective essay, to point out the relevance of an adequate approach to demonstration as an input for the learning of mathematics and the development of teaching and learning processes, as well as some reflections on works linked to the social construction of knowledge, as well as experiences that have been generated and the importance of the problematization of knowledge for its construction and resignification